Lipid Remodeling Reveals the Adaptations of a Marine Diatom to Ocean Acidification - Jin, Peng; Liang, Zhe; Lu, Hua; Pan, Jinmei; Li, Peiyuan; Huang, Quanting; Guo, Yingyan; Zhong, Jiahui; Li, Futian; Wan, Jiaofeng; Overmans, Sebastian; Xia, Jianrong (Frontiers in Microbiology, 2021)
Ocean acidification is recognized as a major anthropogenic perturbation of the modern ocean. While extensive studies have been carried out to explore the short-term physiological responses of phytoplankton to ocean acidification, little is known about their lipidomic responses after a long-term ocean acidification adaptation. Here we perform the lipidomic analysis of a marine diatom Phaeodactylum tricornutum following long-term (~400 days) selection to ocean acidification conditions. We identified a total of 476 lipid metabolites in long-term high CO2 (i.e., ocean acidification condition) and low CO2 (i.e., ambient condition) selected P. tricornutum cells. Our results further show that long-term high CO2 selection triggered substantial changes in lipid metabolites by down- and up-regulating 33 and 42 lipid metabolites. While monogalactosyldiacylglycerol (MGDG) was significantly down-regulated in the long-term high CO2 selected conditions, the majority (~80%) of phosphatidylglycerol (PG) was up-regulated. The tightly coupled regulations (positively or negatively correlated) of significantly regulated lipid metabolites suggest that the lipid remodelling is an organismal adaptation strategy of marine diatoms to ongoing ocean acidification. Since the composition and content of lipids are crucial for marine food quality, and these changes can be transferred to high trophic levels, our results highlight the importance of determining the long-term adaptation of lipids in marine producers in predicting the ecological consequences of climate change.